Personality Similarities and Martial Satisfaction Between Husband and Wife - Liunardi, Julian; Yuwanto, Listyo; Rahaju, Soerjantini (Faculty of Psychology, Universitas Surabaya, 2011)
This study aimed to examine whether there is a relationship in personality similarities and martial satisfaction between husband and wife. The subjects were 50 married working couples (50 husbands and 50 wives) with one or more children under the age of 12, obtained through accidental sampling. Data were collected through questionnaires consisting demographic and open questions, marital satisfaction, and personality. The personality questionnaire was adapted from the Big Five Personality Inventory. The data were analysed with Cramer's V statistical test method as well as the Eta statistical test method to verify the consistency of the results. The results reveal no relationship between couples’ personality similarity to marital satisfaction. Tujuan studi ini adalah mencari hubungan antara kemiripan kepribadian suami-istri dan kepuasan pernikahan. Para subjek adalah 50 pasangan suami istri (50 suami dan 50 istri) yang bekerja dan memiliki satu atau lebih anak berusia di bawah 12 tahun, yang diperoleh melalui accidental sampling. Data diperoleh melalui kuesioner yang terdiri atas pertanyaan demografis dan pertanyaan terbuka, kepuasan pernikahan, dan kepribadian. Kuesioner diadaptasi dari Big Five Personality Inventory. Data dianalisis dengan uji statistik Cramer’s V maupun dengan uji statistik Eta untuk verifikasi konsistensi hasil. Hasil menunjukkan tidak adanya hubungan antara kesamaan kepribadian pasangan dan kepuasan pernikahan.